La calidad del servicio y el grado de satisfacción de los usuarios afiliados a una EPS de la Clínica Materno Infantil del Norte S.A.- Trujillo: 2015. - Fonseca Diaz, Katya Jessica (2015)
This research work entitled “SERVICE QUALITY AND THE DEGREE OF SATISFACTION OF USERS AFFILIATED WITH AN EPS OF CLINIC MOTHER-CHILD NORTH S.A.-TRUJILLO: 2015”; the general objective was: To determine the influence of service quality on the degree of satisfaction of users affiliated to an EPS of Clinic Mother-Child North S.A. - Trujillo: 2015, based on issues of quality, service and user satisfaction. For this research report the design used was descriptive - cross and methods: deductive-inductive, analytic, synthetic and statistical method. In the techniques of data collection the survey was used. From the results obtained, we can highlight that users and/or patients affiliated with a EPS of the clinic, perceived the service quality in general, as a service of high quality, and that the degree of user satisfaction and/or patients is a high degree too, also the best service attribute perceived by users and/or patients is reliability, which refers to the sincere interest in solving problems, promising to do something and stick and proper service first; followed by empathy. These results were the basis for proposing actions to improve user satisfaction and/or patients. For these reasons, it was concluded that the quality of service itself favorably influences the degree of satisfaction of users affiliated with an EPS of Clinic Mother-Child North S.A.-Trujillo: 2015.